Response surface optimization of high antioxidative extraction from Curcuma zedoaria leaves - Abd Gani, Siti Salwa; Azahar, Nur Fauwizah; Mokhtar, Nor Fadzillah (Penerbit Akademia Baru, 2018)
Response surface methodology (RSM) has been fully utilized in this study to model and optimize the extraction conditions for maximum antioxidant compounds activity from Curcuma zedoaria leaves. This work was carried out based on three factor/5 level of central composite rotatable design (CCRD) and three independent variables, namely extraction temperature (60-80 ο C), processing time (80-120min) and solvent concentration (70-90 v/v %). The experimental data was subjected to total antioxidant activity measured by the 1, 1-diphenyl-2-picrylhdrazyl (DPPH)-radical scavenging, β-carotene bleaching (BCB) inhibition as well as ferric ion reducing antioxidant power (FRAP). By using the desirability functions, the optimal conditions were found to be at temperature 75 ο C, 92 min and (90:10 v/v%) ethanol concentration for the highest total antioxidants values for DPPH, BCB and FRAP were 85.76%, 81.35 % and 5.08 mM Fe 2+ g/DW respectively, which closely agreed with the predicted values of 87.59%, 82.29%, 5.25 mM Fe 2+ g/DW respectively. Thus, indicating the suitability of the model employed in RSM to optimizing the extraction conditions.